“Staying isolated indoors means that nobody sees me”: ontological (in)security and living with significant appearance concerns before, during, and “since” COVID-19 - Christian Edwards; Berenice Mahoney; Emma V. Richardson; Beck Lowe (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Though a worldwide period of uncertainty (COVID-19) has “ended”, there exists a legacy of maladaptive experiences among people with significant appearance concerns (SAC) that requires care and attention. Methods Using Giddens’ concept of ontological security, we explored how people experienced their SAC before, during and “since” COVID-19. Qualitative surveys allowed us to capture diverse perspectives from individuals transnationally, analysed with deductive reflexive thematic analysis using ontological security as our theoretical foundation. Results Themes named “More Mirror(ed) Time” and “Locked Out, Shut Down, and Shut Out” gave a contextual grounding for the embodied experiences of this group through times of social restrictions, and the theme “Redefining Relevance” explored the continued legacy of COVID-19 – and continued global uncertainties such as economic hardship and warfare – that impact the wellbeing of people with SAC. Conclusions People with SAC are still “locked out” from essential healthcare support as those providing healthcare are overworked, under-resourced and rely on efficient interactive methods such as tele-health that may be triggers for people with SAC. Care providers may consider expanding appearance concerns verbiage, look to involve trusted others in the care-seeking process, and utilize modalities beyond digital health to support people with SAC.